Relationship Between Altimetric Quality and Along-Track Spatial Resolution for iGNSS-R Sea Surface Altimetry: Example for the Airborne Experiment - Liu, Zongqiang; Zheng, Wei; Wu, Fan; Kang, Guohua; Sun, Xuezhi; Wang, Qiang (Frontiers in Earth Science, 2021)
The altimetric quality and the along-track spatial resolution are the critical parameters to characterize the performance of interferometric global navigation satellite systems reflectometry (iGNSS-R) sea surface altimetry, which is closely related to each other through signal processing time. Among them, the quality of sea surface height (SSH) measurement includes precision and accuracy. In order to obtain higher altimetric quality in the observation area, a longer signal processing time is needed, which will lead to the loss of spatial resolution along the track. In contrast, higher along-track spatial resolution requires more intensive sampling, leading to unsatisfactory altimetric quality. In this study, taking the airborne iGNSS-R observation data as an example, the relationship between the altimetric quality and the along-track spatial resolution is analyzed from the perspectives of precision and accuracy. The results indicate that the reduction in the along-track spatial resolution will improve the altimetric quality. The accuracy range is 0.28–0.73 m, and the precision range is 0.24–0.65 m. However, this change is not linear, and the degree of altimetric quality improvement will decrease as the along-track spatial resolution worsens. The research results in this paper can provide a scientific reference for the configuration of parameters for future spaceborne iGNSS-R altimetry missions.